Precision Oncology and Gender Medicine – Moving Forward, Slowly but Surely - Berna C. Özdemir; Anna Dorothea Wagner (healthbook TIMES. Oncology Hematology)
Sex and gender aspects are gaining attention in oncology. Epidemiological studies show that women have reduced risk and better outcome than men in a wide range of cancer types. Melanoma is a prime example of cancer with significant female survival advantage across different stages and independent of various prognostic factors. In addition, accumulating evidence shows that women are more susceptible to the toxicity of different types of drugs. Also, considering their differences in body composition, sex-specific dosing strategies, taking into account a patient’s fat-free body mass could improve the balance between efficacy and toxicity of anticancer therapies in men and women.